Impact of oil on groundwater chemical composition; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Brakorenko N. N. Nataliya Nikolaevna (Hydrogeology and Engineering Geology. Geoinformation Systems in Hydrogeology and Engineering Geology, 2015)
Title screen